Zespół metaboliczny jako ujęcie globalnego ryzyka miażdżycy i jej powikłań: krytyczne refleksje i praktyczne wnioski - Tatoń, Jan; Bernas, Małgorzata; Szczeklik-Kumala, Zofia (Przewodnik Lekarza/Guide for GPs, 2009)
The concept of the metabolic syndrome is based on the long history and efforts of many studies. It refers to the common, simultaneous appearance of many metabolic risk factors of atherosclerosis and of its complications – mostly in persons with abdominal obesity and resistance to insulin. Its aetiological and pathogenetic interpretation continues however to be vividly discussed. One may also note opinions not accepting the concept of the metabolic syndrome. This situation creates the existence of several different definitions, which could be divided into “adiposocentric” and “diabetocentric”. There are also many additional, atherogenic risk factors, which are not included in existing definitions. The reason for introduction of the metabolic syndrome approach was the practical need for assessing the clinical significance of global risk due to simultaneous existence of high specific risk mechanisms in a single individual. The academic discussion of many basic definitions creates however several difficulties in the real world of preventive clinical practice. The paper presents these problems and emphasises the necessity of enlarging the diagnostics and therapy of the metabolic syndrome beyond the classical definitions in individual cases.